Growth and Nutrient Content Variation of Groundnut Arachis hypogaea L. under Vermicompost Application - and R. Thangadurai, T. Ravi mycin, M. Lenin*, G. Selvakumar (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 2pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Plant nutrients are essential for the production of crops and healthy food in the worlds expanding population. Plant nutrients are therefore a vital component of sustainable agriculture.Â The use of chemical fertilizers, contributes largely depletion of fossils fuels, generation of carbon dioxide and contamination of water resource it leads to loss of soil fertility due to imbalance use of fertilizers that has adversely impacted agriculture productivity and causes of soil degradation. Now there is a growing realization that the adoption of ecological and sustainable farming practices can only reverse the declining trend in the global productivity and environmental protection. So the present study was carried out the impact of vermicompost on groundnut (Arachis hypogaea L.). Three experimental plots were prepared control, T1- 1 ton h-1; T2-2 ton h-1; T3- 3 ton h-1 and T4- 4 ton h-1 to test the plant production patterns, under field conditions. The morphological parameters such as root length, shoot length, number of leaves, fresh weight, dry weight and root nodules, yield parameters and the nutrient content viz., nitrogen, phosphorus, potassium were analyzed at 120 days of plants.Â All the morphological parameters and nutrient contents were higher in T4 treatments, when compared with other treatments.Â